Sindikat Peredaran Narkotika Di Lembaga Permasyarakatan - Mespy M Selanno; Iqbal Taufik (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Narcotics are becoming more and more rampant, after the police managed to capture the prisoners in Class II A Ambon Prisons.Purposes of the Research: The purpose of this study was to determine the causes of drug trafficking in the Class II A Ambon prison. Methods of the Research: The research method used is normative juridical where legal norms are used as the basis for knowing the illicit trafficking of narcotics in public institutions.Results of the Research: The results showed that the role of prisons in efforts to enforce criminal law and with sentencing is to return the prisoners to the community so that they can mingle and play a role again as free and responsible members of society. Correctional institutions as a place of guidance for inmates to improve themselves, do not repeat criminal acts so that they can be accepted back by the community, have turned into the biggest drug trafficking hotbeds and at the same time new drug dealers. In fact, most of the drug trafficking in Indonesia is controlled from prisons. The cause of illicit drug trafficking among the Class II A Ambon Correctional Institutions is also caused by the lack of supervision and control by the Ambon Class II A Prison officers themselves. The still use of telecommunication tools among the public will find communication findings with people outside prisons (narcotics couriers), so that it will directly facilitate the action of illicit narcotics trafficking. There is also the involvement of unscrupulous correctional officers as a syndicate of illicit narcotics trafficking and this is also a trigger for the increase in the illicit circulation of narcotics among the community.